2016
DOI: 10.1093/mnrasl/slv195
|View full text |Cite
|
Sign up to set email alerts
|

Equipartition and cosmic ray energy densities in central molecular zones of starbursts

Abstract: The energy densities in magnetic fields and cosmic rays (CRs) in galaxies are often assumed to be in equipartition, allowing for an indirect estimate of the magnetic field strength from the observed radio synchrotron spectrum. However, both primary and secondary CRs contribute to the synchrotron spectrum, and the CR electrons also loose energy via bremsstrahlung and inverse Compton. While classical equipartition formulae avoid these intricacies, there have been recent revisions that account for the extreme con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 37 publications
4
47
0
Order By: Relevance
“…We evaluate τ eff , Φ 0 , Υ 0 , and the midplane CR energy density U(0) = −Φ 0 /u (0) for β = 1/4 and the fiducial parameters for each of our galaxies in Table 1, using E CR,SN = 10 50 erg and M SN = 100 M , i.e., assuming 1 supernova per 100 M of stars formed, with that supernova putting ≈ 10% of its energy into CRs. For our fiducial parameters, CR midplane energy densities are of order 1 − 5 keV cm −3 , similar to previously-published estimates (e.g., Yoast-Hull et al 2016); however, we remind readers that we have explicitly assumed that advective escape of CRs is negligible, so if advective escape is significant the true energy densities may be somewhat lower. These energy densities are roughly a factor of 10 3 − 10 4 larger than in the Milky Way.…”
Section: Solutionssupporting
confidence: 85%
“…We evaluate τ eff , Φ 0 , Υ 0 , and the midplane CR energy density U(0) = −Φ 0 /u (0) for β = 1/4 and the fiducial parameters for each of our galaxies in Table 1, using E CR,SN = 10 50 erg and M SN = 100 M , i.e., assuming 1 supernova per 100 M of stars formed, with that supernova putting ≈ 10% of its energy into CRs. For our fiducial parameters, CR midplane energy densities are of order 1 − 5 keV cm −3 , similar to previously-published estimates (e.g., Yoast-Hull et al 2016); however, we remind readers that we have explicitly assumed that advective escape of CRs is negligible, so if advective escape is significant the true energy densities may be somewhat lower. These energy densities are roughly a factor of 10 3 − 10 4 larger than in the Milky Way.…”
Section: Solutionssupporting
confidence: 85%
“…4-a,c show a combined effect from CREs and B, i.e, from the nonthermal ISM. We also stress that γ-ray observations confirm the validity of the CRE-B equipartition for Σ SFR < 100 M ⊙ yr −1 kpc −2 [41], and hence for the nuclear ring of NGC 1097 (with Σ SFR ≃ 2 M ⊙ yr −1 kpc −2 ).…”
Section: What Controls Nuclear Star Formationsupporting
confidence: 73%
“…There is also the possibility of the system being immersed in a strong cosmic ray background, however such environmental interactions are beyond the scope of this work. However, Yoast-Hull et al (2016) have found that the cosmic ray energy in nuclear starbursts tends to be considerably smaller than the magnetic field energy, suggesting that even in the full picture with a realistic galactic environment cosmic rays should not greatly influence the overall dynamics of a collapsing GMC.…”
Section: Metallicitymentioning
confidence: 99%